Faith and Ethnicity: The Fusion of Ulama, Chinese, and Javanese in the 1750 Sabil War of Lasem - Abdul Aziz (Buletin Al-Turas, 2026)
Purpose This research aimed to analyze the contributions of three pivotal figures—Kiai Ali Badhawi, Oei Ing Kiat, and Raden Panji Marghana—in the Sabil War of Lasem. The study sought to explore how these leaders leveraged charismatic and traditional authority to build alliances across ethnic divides in resistance against VOC colonization. Method This study employed a historical research method, comprising four stages: heuristics, verification, interpretation, and historiography. Primary and secondary sources, such as Carita Sejarah Lasem and Sabda Badra-Santi, were analyzed to understand the leadership dynamics and social networks during the Sabil War. The research applied Weber’s leadership theory and social capital framework to examine cross-ethnic coalitions.          Results/findings The study revealed that the three leaders used charismatic and traditional authority to foster a multi-ethnic resistance. Their ability to mobilize diverse groups was supported by strong social networks, transcending ethnic boundaries, which played a critical role in organizing the resistance against VOC colonial forces.     Conclusion                   The study concluded that the fluid, kinship-based, and syncretic leadership practices—strengthened by the formation of collective identity in contemporary crowd psychology—challenge the universality of Weber’s Eurocentric ideal types. Future research should therefore conduct a critical dialogue between Weberian theory, the Social Identity Approach, and local anti-colonial experiences.